ECONOMIC AND INSTITUTIONAL CONDITIONS ON TOWNS ADJACENTS TO ALBERTO MANUEL BRENES BIOLOGICAL RESERVE - Guido Granados, Ismael G. (2025)
The knowledge about the economic and institutional conditions in the communities around the protected areas is essential to strength the conservation effort that is running into them and also to achieve the best conditions of the inhabitants of the communities. Thus, the reality shows on these topics presents the periphery of the Alberto Manuel Brenes Biological Reserve, where per capita income is so low that leads the population to locate in extreme poverty. Meanwhile in these places there is no proper management and disposal of solid waste. At institutional level there is a wide electricity coverage, but not so for access to telephone and mobile telephone, and Internet.